'Getting to know 'them' changed my opinion': intercultural competence among Jewish and Arab graduate students. Issue 10 (25th November 2020) - Lev Ari, Lilach; Husisi-Sabek, Rabia
ABSTRACT: The purpose of this study was to examine the impact of intercultural encounters with the Other (between Jews and Arabs) during graduate studies, at colleges of education and university education departments, on the level of intercultural competence reported by them. Intercultural competence means a long-term change in the level of knowledge, feelings, attitudes and actual behavior that enables positive interactions with members of other cultural groups. In the study, 436 graduate students, completed survey questionnaires, which included mostly closed-ended questions. The findings indicate that the experience of encounter has a significant impact on the development of intercultural competence: A perceived inclusive atmosphere, positive interactions among students, and particularly contents acquired in the institution, which had an impact on all components of intercultural competence for both Jews and Arabs, but to a higher degree among Arabs. All that, alongside with off-campus interactions with 'others' and positive attitudes towards multiculturalism. The importance of this study is in its possible contribution to the body of knowledge regarding encounters with 'others' in higher education institutes (universities and colleges) and to developing policy trajectories towards intercultural competence among graduate students, including those who experience deep political conflicts in their countries.